Dietary Lasia spinosa Thw. improves reproductive performance of aged roosters - Hong, Yongxing; Zhang, Lang; Liu, Xingting; Wu, Sile; Wen, Jian; Sun, Haodong; Tian, Kui; Jia, Xiaoxuan; Liao, Yuying; Suthikrai, Wanwipa; Tharasanit, Theerawat; Lu, Yangqing (Frontiers in Nutrition, 2022)
Owing to the widespread application of artificial insemination, breeder animals are an important resource in breeding farms. However, roosters typically demonstrate a decline in reproductive performance with age, and the shortened reproductive lifespan is responsible for economic loss. Lasia spinosa Thw. (LST) reportedly improved reproductive capacity in male rodents. The objective of this study was to investigate the effects of LST on the reproductive performance of aged roosters. Dietary supplementation with LST significantly increased semen volume, sperm motility, and concentration; the most potent effects were observed in the treatment group that received dietary supplementation with 2% LST. Administration of 2% LST resulted in significant improvements in the weight of the testes, diameter of the seminiferous tubule, and height of the seminiferous tubule epithelium. We observed a significant increase in the fructose and glucose concentration in the testis and seminal plasma; furthermore, a significant increase was observed in the α-glycosidase levels in the testis and spermatozoa. However, the monoaldehyde levels in the spermatozoa appeared to decline significantly. RNA-seq analysis revealed that 34 and 16 unigenes were upregulated and downregulated, respectively, in testicular tissues from roosters who received dietary supplementation of 2% LST. The assigned functions of the unigenes revealed that LST primarily influenced the mechanisms underlying catalytic activity and cellular processes. Kyoto Encyclopedia of Genes and Genomes enrichment analysis suggested that spermatogenesis-related pathways were significantly enriched, including ABC transporters, ribosome biogenesis in eukaryotes, VEGF, cAMP, and ErbB signaling pathway.